PENINGKATAN PENGETAHUNAN IBU TENTANG GANGGUAN PENDENGARAN PADA BALITA - Awalia, Naila Ridha; Daud, Ruslia; Efendi, M.Riyan; Lestari, Tutik (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Hearing loss is a condition in which a person's ability to hear is disrupted. Symptoms of hearing loss include unclear or even inaudible sounds, difficulty communicating, and the risk of disrupting a person's activities. The purpose of the activity is to provide knowledge about hearing loss and early prevention related to hearing problems in children/toddlers. The activity was carried out on May 2, 2025 in Bobo Village, Jailolo District, West Halmahera Regency, targeting 14 mothers who have toddlers. The results of the activity showed that children responded to sounds from both their parents and their surroundings. A child's ability to respond to sounds in the surrounding environment is an important indicator in sensory and language development. A good response to sound indicates that the child's hearing and attention are developing normally.